2014
DOI: 10.1111/iej.12327
|View full text |Cite
|
Sign up to set email alerts
|

Skin reactions amongst Greek endodontists: a national questionnaire survey

Abstract: Approximately one-third of participants reported skin reactions. History of atopy and dermal eczema as well as gender was significantly associated with such reactions. The use of powder-free latex gloves instead of powdered ones was the measure most frequently adopted to manage reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…According to our survey results, the skin of the hands requires particular care and protective measures as most of the lesions (96%) occurred on the hands, corresponding to a Greek survey of dental professionals, which is expected since hands are highly exposed to irritants and allergens due to the nature of dental work ( 14 ).…”
Section: Discussionmentioning
confidence: 64%
“…According to our survey results, the skin of the hands requires particular care and protective measures as most of the lesions (96%) occurred on the hands, corresponding to a Greek survey of dental professionals, which is expected since hands are highly exposed to irritants and allergens due to the nature of dental work ( 14 ).…”
Section: Discussionmentioning
confidence: 64%
“…Contact with dental materials and disinfectants, wearing of protective gloves, and frequent hand washing cause damage to the skin barrier that can result in dry skin and hand eczema. In most cases, work‐related skin lesions in dental staff manifest as contact reactions in terms of irritant contact dermatitis, allergic contact dermatitis, or contact urticaria, commonly on the hands but also on other body parts (eg, forearms, face, and neck) . Studies on the prevalence of hand eczema in dental personnel have been conducted in Sweden, Denmark, Finland, the United States, and Poland …”
Section: Introductionmentioning
confidence: 99%
“…In most cases, work-related skin lesions in dental staff manifest as contact reactions in terms of irritant contact dermatitis, allergic contact dermatitis, or contact urticaria, commonly on the hands but also on other body parts (eg, forearms, face, and neck). [4][5][6][7][8][9] Studies on the prevalence of hand eczema in dental personnel have been conducted in Sweden, [10][11][12] Denmark, 13 Finland, 6 the United States, 14 and Poland. 15 These skin problems may begin during student training and education.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted among dentists in Thailand revealed a 1‐year prevalence of 21.9%, 13 which was lower than in studies from Norway and New Zealand with a 1‐year prevalence of 45% 16 and 47%, 14 respectively. The 5‐year prevalence of skin reactions among Greek endodontists was estimated to be 32.5%, while 82.1% of endodontists considered the reactions to be associated with the dental occupation 17 . Although most of the studies do not present data on point prevalence, making the comparison difficult, it seems that the rate of work‐related skin symptoms in Bulgarian dentists is high.…”
Section: Discussionmentioning
confidence: 99%